Regulation of Sirtuin Function by Posttranslational Modifications - Flick, Franziska; Lüscher, Bernhard (Frontiers in Pharmacology, 2012)
Sirtuins are homologs of the yeast silencing information regulator 2 (Sir2) protein, an NAD+-dependent (histone) deacetylase. In mammals 7 different sirtuins, SIRT1-7, have been identified, which share a common catalytic core domain but possess distinct N- and C-terminal extensions. This core domain elicits NAD+-dependent deacetylase and in some cases also ADP-ribosyltransferase, demalonylase, and desuccinylase activities. Sirtuins have been implicated in key cellular processes, including cell survival, autophagy, apoptosis, gene transcription, DNA repair, stress response, and genome stability. In addition some sirtuins are associated with disease, including cancer and neurodegeneration. These findings suggest strongly that sirtuins are tightly controlled and potentially responsive to different signal transduction pathways. Here, we review the posttranslational regulation mechanisms of sirtuins and discuss their relevance regarding the physiological processes, with which the different sirtuins are associated. The available data suggest that the N- and C-terminal extensions are the targets of posttranslational modifications that can affect the functions of sirtuins. Mechanistically this can be explained by the interaction of these extensions with the catalytic core domain, which appears to be controlled by posttranslational modifications at least in some cases. In contrast little is known about posttranslational modifications and regulation of the catalytic domain itself. Together these findings point to key regulatory roles of the N- and C-terminal extensions in controlling sirtuin functions, thus connecting these regulators to different signaling pathways.